2021
DOI: 10.1111/1467-8489.12420
|View full text |Cite
|
Sign up to set email alerts
|

Explaining permanent and temporary water market trade patterns within local areas in the southern Murray–Darling Basin

Abstract: The southern Murray-Darling Basin of Australia has the world's largest and most sophisticated water markets. However, there has been little study on the drivers of permanent and temporary water market movements within local areas, or the substitution effects between groundwater and surface-water extraction over time. This topic is important as it is often claimed that water market trade patterns (especially selling large amounts of permanent water) are associated with rural decline. This study uses random-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Nauges et al (2016) established horticultural irrigators used temporary water trading because they were averse to the risk of large losses (downside risk), while broadacre irrigators used water temporary trading as they were averse to profit variability (variance). Haensch et al (2021) found no statistically significant association of poorer socio‐economic areas with water allocation trade. They suggested water allocation trading was more significantly associated with water scarcity, confirming that markets provide an important adaptive tool for irrigators in response to unfavourable conditions.…”
Section: Australian Water Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nauges et al (2016) established horticultural irrigators used temporary water trading because they were averse to the risk of large losses (downside risk), while broadacre irrigators used water temporary trading as they were averse to profit variability (variance). Haensch et al (2021) found no statistically significant association of poorer socio‐economic areas with water allocation trade. They suggested water allocation trading was more significantly associated with water scarcity, confirming that markets provide an important adaptive tool for irrigators in response to unfavourable conditions.…”
Section: Australian Water Marketsmentioning
confidence: 99%
“…This finding indicates that, at some point, selling more permanent water entitlements may be a negative financial strategy for an individual farm if the desire is to continue irrigation, and more research is needed in this area using longitudinal panel datasets. Haensch et al (2021) investigated the drivers of permanent water trade and found that key influences on the volumes of entitlements sold included net rainfall, groundwater use and dryland salinity -while water entitlement purchase volumes were far more likely to be associated with water market prices, location and soil productivity. No significant association between socio-economic status and amount of water entitlements sold was found, although there did seem to be a significant association between more disadvantaged areas and higher volumes of water entitlements purchased (which is the opposite of the belief that selling water entitlements disadvantages local areas).…”
Section: Permanent Trade Impacts On Farm Profitabilitymentioning
confidence: 99%